Adaptive Power Regulation of Street Lights Using Light Sensor Thresholding: A Proteus-Based Simulation Study - Maya Itasari; Zainal Akbar (Inspiration: Jurnal Teknologi Informasi dan Komunikasi, 2025)
This paper presents the design and simulation of a street lighting power control system based on PWM modulation integrated with ambient light sensing. The simulation circuit consists of a DC-DC converter, an Arduino Nano microcontroller, an IRFZ44N MOSFET as a switching device, an INA219 sensor for current and voltage monitoring, an LDR (Light Dependent Resistor) for ambient light detection, and a street lamp module as the load. PWM duty cycle variation, ranging from 10% to 100%, was simulated to analyze its effect on the voltage, current, and power characteristics of the system. Additionally, an LDR sensor was employed to dynamically adjust the PWM output based on external light intensity, simulating vehicle headlights or environmental lighting changes. The simulation results showed that the maximum power consumption reached 5.490 W at 100% PWM. By implementing a scheduled PWM adjustment (50%-100%) combined with LDR-based control, the system achieved an estimated energy efficiency improvement of over 40% compared to conventional constant illumination at full brightness. The proposed design demonstrates the potential for significant energy savings and offers an effective solution for developing intelligent and energy-efficient street lighting systems in smart city applications